2014
DOI: 10.1124/jpet.114.212928
|View full text |Cite
|
Sign up to set email alerts
|

Ramipril Protects the Endothelium from High Glucose–Induced Dysfunction through CaMKKβ/AMPK and Heme Oxygenase-1 Activation

Abstract: This study aims to investigate the effects of ramipril (RPL) on endothelial dysfunction associated with diabetes mellitus using cultured human aortic endothelial cells (HAECs) and a type 2 diabetic animal model. The effect of RPL on vasodilatory function in fat-fed, streptozotocin-treated rats was assessed. RPL treatment of 8 weeks alleviated insulin resistance and inhibited the decrease in endothelium-dependent vasodilation in diabetic rats. RPL treatment also reduced serum advanced glycation end products (AG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 56 publications
(53 reference statements)
2
11
0
1
Order By: Relevance
“…Previous studies in similar models of T2DM as used in the current study demonstrated decreased vascular relaxation in the posterior ciliary artery (Davidson et al, 2012) and epineurial arterioles (Davidson et al, 2011), at week 12, and in the aorta at week 6–8 (Zhang et al, 2013; Tian et al, 2014; Latha et al, 2013). Several studies in animal models of vasculogenic ED reported endothelial dysfunction in the penile vascular bed occurring prior to this effect in the aorta, coronary, and mesenteric arteries, supporting our findings.…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies in similar models of T2DM as used in the current study demonstrated decreased vascular relaxation in the posterior ciliary artery (Davidson et al, 2012) and epineurial arterioles (Davidson et al, 2011), at week 12, and in the aorta at week 6–8 (Zhang et al, 2013; Tian et al, 2014; Latha et al, 2013). Several studies in animal models of vasculogenic ED reported endothelial dysfunction in the penile vascular bed occurring prior to this effect in the aorta, coronary, and mesenteric arteries, supporting our findings.…”
Section: Discussionsupporting
confidence: 64%
“…,b); (iii) angiotensin‐converting enzyme (ACE1) inhibitors (Tian et al . ); (iv) antihypertensive therapy (Lüscher et al . , Kang et al .…”
Section: Nitric Oxidementioning
confidence: 99%
“…, Tian et al . ); (ix) reduced presence of apelin (Grisk , Zhong et al . ); (x) altered metabolism in the endothelial cells (De Zeeuw et al .…”
Section: Nitric Oxidementioning
confidence: 99%
“…For instance, it is reported that mollugin has potential antioxidant and anti-inflammatory effects (21) that may involve in aortic endothelial protection against hyperglycemic environment. Similarly, it is reported that many agents such as, Propolise, Ramipril, and Hespiridin protect endothelium against damage induced by hyperglycemic environment through their antioxidant activities (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%